2016
DOI: 10.1016/j.scitotenv.2016.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Black pine (Pinus nigra) barks as biomonitors of airborne mercury pollution

Abstract: Tree barks are relevant interfaces between plants and the external environment, and can effectively retain airborne particles and elements at their surface. In this paper we have studied the distribution of mercury (Hg) in soils and in black pine (Pinus nigra) barks from the Mt. Amiata Hg district in southern Tuscany (Italy), where past Hg mining and present-day geothermal power plants affect local atmospheric Hg concentration, posing serious environmental concerns. Barks collected in heavily Hg-polluted areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 76 publications
4
72
0
1
Order By: Relevance
“…Janta et al (2016) reported that concentrations of some metals, including Cr, Cu, Pb, and Zn, were highest in the cork layer of Cassia fistula bark, decreased in the second and third layers (phloem), and increased in the innermost layer (vascular cambium) [37]. Similar patterns of content gradients were observed for Hg in Pinus nigra bark [41].…”
Section: Elemental Analysis Of Tree Barkmentioning
confidence: 74%
See 1 more Smart Citation
“…Janta et al (2016) reported that concentrations of some metals, including Cr, Cu, Pb, and Zn, were highest in the cork layer of Cassia fistula bark, decreased in the second and third layers (phloem), and increased in the innermost layer (vascular cambium) [37]. Similar patterns of content gradients were observed for Hg in Pinus nigra bark [41].…”
Section: Elemental Analysis Of Tree Barkmentioning
confidence: 74%
“…Bellis et al (2003) proved that the bark of Japanese oaks can be suitable for monitoring the historical change in atmospheric arsenic deposition in the vicinity of industrial sites [61]. Also in the areas of mining, recent studies of Chiarantini et al (2016) have shown that black pine bark can be successfully used to determine air pollution by mercury compounds [41]. Research conducted by Conte et al (2016) confirmed the possibility of using the bark of the Slippery Elm tree to detect uranium from nuclear fuel [14].…”
Section: Elemental Analysis Of Tree Barkmentioning
confidence: 99%
“…After that, significant increasing trend was revealed in tree rings with two order of magnitude change. Overall, Hg concentration at both sites showed the highest values located in the outmost rings, which may reflect the potential impacts of higher Hg concentration of tree barks [9].…”
mentioning
confidence: 87%
“…1b). We estimated the increasing rates after the World War Ⅱ without the consideration of the highest Hg values from the outmost five rings due to evident impact by bark [9]. The results revealed that the increasing rates were 0.24 and 0.08 ng g À1 per 10 years after World War Ⅱ at the TS and KLD site, respectively.…”
mentioning
confidence: 99%
“…Juvenile mangroves can show the symptoms of Hg poisoning through loss of turgor, epinasty, leaf abscission, chlorosis and blackening of leaf and stem, if its concentration exceeds 500 mg Kg -1 in the soil (Walsh et al, 1979).When Hg replaces other metal ions in the photosynthetic machinery, there will be a decline in photosynthetic rate (Huang and Wang, 2010). Among plant tissues, bark can represent the sink of Hg through atmospheric deposition, surface absorption and binding to thiol groups and tannins inside the tissue (Serbula et al, 2012;Chiarantini et al, 2017;Chiarantini et al, 2016) As plants are at the base of the trophic chain, it is fundamental to consider Hg concentration (hereafter referred to as [Hg]) in plants, together with sediment and associated fauna. Among the mangrove macro-benthic invertebrates, molluscs are well recognized for their economic potential and relationship with vegetation/edaphic gradients (Bosire et al, 2008;Kon et al, 2010;Chen and Ye, 2011;Andreetta Fig.…”
Section: Introductionmentioning
confidence: 99%